2006
DOI: 10.1007/s00134-005-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Saline volume in transvesical intra-abdominal pressure measurement: enough is enough

Abstract: Using 50 or 100 ml of saline for IAP measurement in critically ill patients results in higher IAP values compared with the use of 10 ml, and possibly, in overestimation of the incidence of intra-abdominal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 15 publications
6
60
0
1
Order By: Relevance
“…Because of the potential for activation of the detrusor muscle, several investigators have advocated the use of a minimal volume to ensure conduction of the fluid wave. 30 Our findings indicate that reproducible IBP measurements can be obtained without instilling any sterile saline into the bladder.…”
Section: Recommendations For Volume Of Saline Instilledsupporting
confidence: 54%
“…Because of the potential for activation of the detrusor muscle, several investigators have advocated the use of a minimal volume to ensure conduction of the fluid wave. 30 Our findings indicate that reproducible IBP measurements can be obtained without instilling any sterile saline into the bladder.…”
Section: Recommendations For Volume Of Saline Instilledsupporting
confidence: 54%
“…The instillation volume for intermittent IAP measurement used in different studies varies significantly from 50 to 250 mL. However, De Waele et al revealed that the minimal volume required to transmit the pressure signal was 10 mL (29). Recently, Malbrain and Deeren gradually increasing instillation volumes found that the actual IAP may be overestimated with instillation volumes over 50 mL and the volume up to 25 mL is sufficient (30).…”
Section: Discussionmentioning
confidence: 99%
“…Our present study protocol was based on these studies. Recently, however, a study was published in which priming with 50 and 100 ml increased the measured IVP compared to 10 ml [20]. Unfortunately, actual IAP was not measured and used as a reference.…”
Section: Discussionmentioning
confidence: 99%